Toward a Culturally Relevant and Spiritually Grounded Theory of Teaching for Social Transformation and Transformational Learning - Elizabeth J. Tisdell; Derise Tolliver; Silvia Villa (Adult Education Research Conference, 2001)
This paper explores what spirituality offers to teaching for social transformation and cultural relevance. We ground our discussion in and beyond the adult education literature, and in our experience as three women of different race and ethnic identities who bring elements of spirituality to our own practice.